A novel A33 promoter-based conditionally replicative adenovirus suppresses tumor growth and eradicates hepatic metastases in human colon cancer models - Cafferata, Eduardo G. (2009)
Purpose: A33 antigen is a membrane-bound protein expressed in intestinal epithelium that is overexpressed in 95% of primary and metastatic colorectal carcinomas but is absent in most epithelial tissues and tumor types. We hypothesized that A33 promoter might be useful in the design of a conditionally replicative adenovirus for the treatment of colorectal cancer (CRC). Experimental Design: We cloned an A33 promoter fragment (A33Pr) that extends from -105 to +307 bp. Using luciferase activity as a reporter gene, we showed that A33Pr was active inCRC cell lines. We next constructed a conditionally replicative adenovirus named AV22EL where E1A was placed under the control of A33Pr. The tumor-specific oncolytic effect of AV22EL was investigated both in vitro and in vivo. Results: AV22EL induced specific in vitro lysis of human CRC cell lines that expressed A33 and have negligible lytic capacity on cells that lacked or hadminimal A33 expression, including normal human colonic cells. In vivo, a marked reduction of tumor growth and increased long-term survival rates were observed in nude mice xenografted with s.c. CRC tumors. Combination with 5-fluorouracil induced an additive effect in vitro with no toxic effects in vivo. Remarkably, AV22EL completely eliminated established hepatic metastases in >90% of mice and restored hepatic function according to biochemical parameters. Its systemic administration induced E1A expression only in the hepatic metastasis but not in normal organs. Conclusions: These data show that AV22EL is a stringently regulated and potent oncolytic agent for the treatment of CRC.